Testing and analysing the material properties of 316L-CuCrZr multi-material manufactured by laser powder bed fusion - Iizuka, Olivia (My University, 2025)
Laser powder bed fusion of metals (PBF-LB/M) is a method of additive manufacturing (AM), also known as industrial 3D printing, where metal powder is melted and fused into a solid metal layer by layer. PBF-LB/M is a promising technology in the field of multi-material manufacturing, where components are manufactured with two or more discrete materials. Multi-material AM shows potential in applications where complex geometries are used to optimise the function of the manufactured component. This thesis researches the suitability of 316L stainless steel and CuCrZr alloy in multi-material PBF-LB/M. It provides information on the suitable parameters for PBF-LB/M and post-processing of CuCrZr-316L multi-material. The thesis consists of a literature review and the experimental part. The literature review provides information on the properties and behaviour of the studied materials, and data on the suitable PBF-LB/M, post-processing and material testing parameters and procedures for 316L-CuCrZr multi-material. The experimental part was used to evaluate the material properties of as-built and post-processed PBF-LB/Med 316L-CuCrZr by conducting several material property tests, including: metallographic analysis, microhardness testing, geometrical accuracy measurements, corrosion resistance testing, and thermal and electrical conductivity testing. The experimental part revealed information about the different material properties and defects, such as cracking and porosity of 316L-CuCrZr manufactured with varying PBF-LB/M and post-process parameters. The metallographic analysis found information on the mixing and bonding of 316L-CuCrZr material during the PBF-LB/M process. Heat treatment was revealed to cause cracking in the 316L-CuCrZr interface, due to differences in thermal expansion coefficients between the discrete materials. The heat-treatment was also observed to increase the microhardness, corrosion rate and thermal conductivity of the 316L-CuCrZr. The increase of microhardness and material conductivity was hypothesised to be a result of precipitation in CuCrZr, whereas the corrosion rate was suspected to have increased due to changed corrosion potential values of the discrete 316L and CuCrZr and the cracking in the 316L-CuCrZr interface. The geometry of the multi-material revealed marginal misalignment between the 316L and CuCrZr geometries, which was most likely caused by horizontal tilting of the 316L material during the material changing in the PBF-LB/M process. Therefore, the thesis was able to research the PBF-LB/M of 316L-CuCrZr multi-material by gathering data on the PBF-LB/M parameters, post-processing and their effect on the material properties of the 316L-CuCrZr multi-material through literature research and empirical experimentation.
Keywords: Additive manufacturing, laser powder bed fusion, multi-material, bimetallic additive manufacturing, 316L, CuCrZr, heat treatment, material